2019
DOI: 10.4314/rjmhs.v2i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effects of burnout on patients and its management among nurses in the Intensive Care Unit and Emergency Department of a Rwandan University Teaching Hospital

Abstract: BackgroundThe level of burnout among nurses working in the Intensive Care Unit (ICU) and Emergency Department (ED) is high, which adversely affects health and work-related outcomes for both nurses and patients. Little is known about burnout among ICU and ED nurses in Rwanda. ObjectiveTo explore the perceived effects of burnout among nurses and its management at a referral hospital in Rwanda. Methods A qualitative study design was carried out using focus groups. A purposive sample of six ICU and six ED nurses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While there is paucity of studies examining physicians' perception of burnout's impact on patient safety, a majority of burnout-prone healthcare workers surveyed in a tertiary health institution in Rwanda aver to suboptimal patient care, medical errors and poor outcome which they attributed to burnout [22].…”
Section: Discussionmentioning
confidence: 99%
“…While there is paucity of studies examining physicians' perception of burnout's impact on patient safety, a majority of burnout-prone healthcare workers surveyed in a tertiary health institution in Rwanda aver to suboptimal patient care, medical errors and poor outcome which they attributed to burnout [22].…”
Section: Discussionmentioning
confidence: 99%
“…Among healthcare workers, burnout has been indicated to influence suboptimal patient care, medical errors and adverse outcomes. 11,12 We found that high exhaustion was reported in 65.6% of study participants, while high disengagement was noted in 47.3%. Frequency of burnout was reported in 40.9% of study participants.…”
Section: Discussionmentioning
confidence: 73%
“…8 These cut-off scores were adopted from previous research done. 12 The main outcome measured was burnout. Burnout was described as "high exhaustion" and "high disengagement".…”
Section: Methodsmentioning
confidence: 99%
“…25 Conversely, systematic guidelines lead to improvement in providing quality care, enhance appropriateness of clinical procedures and decisions, increase patients' safety and outcomes of clinical care, and decrease the cost and time. 26,27 The current study suggested some strategies to minimise the delay in TR band removal to prevent complications associated with prolonged compression. These include inservice training of staff nurses, policy development, and ensuring an adequate nurse-to-patient ratio.…”
Section: Discussionmentioning
confidence: 90%